IMPLEMENTATION OF ECO-ORIENTED PEDAGOGICAL TECHNOLOGIES IN THE PROFESSIONAL TRAINING OF FUTURE QUALIFIED WORKERS IN THE CONSTRUCTION, AGRICULTURAL AND RESTAURANT INDUSTRY (Innovative professional education, 2024)
The algorithm and expediency of introducing eco-oriented pedagogical technologies into professional training of future qualified workers in the construction, agrarian and restaurant industries are analyzed in the context of scientific research of the laboratory of vocational training technologies.
Keywords: professional education, eco-oriented pedagogical technologies, professional training, future skilled workers, training